PEMBERDAYAAN MASYARAKAT JATINANGOR: PEDULI KEGAWATDARURATAN JANTUNG – SUDDEN CARDIAC ARREST - Aan Nur'aeni; Ristina Mirwanti; Anastasia Anna (Bagimu Negeri, 2018)
There are many cases of Sudden Cardiac Arrest (SCA) in the community that cannot be rescued, because they did not get the proper and fast action due to ignorance and incompetence of the community. The purpose of this training was  increasing the knowledge, attitudes, intentions, and abilities of the community in identifying and handling SCA in Cileles Village, Jatinangor District. The community service activities were integrated with student’s KKN activities. This activity was carried out starting from the initial assessment related to the CPR ability of  the community, socialization to KKN students, preparation of materials and learning media, the implementation of socialization and training activities for the community, and also this evaluation. At the implementation stage, 33 training participants participated. Pre-test and post-test measurements were carried out with the response rate as much as 90.9%. As much as 53.3% of respondents had never received information about cardiac arrest, and 93.3% had never received information about CPR before. After training, the respondents' average knowledge score was 75.7. On the attitude aspect, before training, 90% of respondents supported the implementation of CPR and after training, 96.7% of participants supported the implementation of CPR. Meanwhile, before the training, no participants intended to do CPR if they found victims of SCA, but 100% of participants intended to do CPR after training. There was an increase in knowledge, attitudes, and community intentions related to the handling of cardiac emergencies, especially cardiac arrest. This was an indication that CPR will be carried out by respondents if they found victims of SCA. Similar training needs to be conducted periodically to prevent the decline in knowledge or skills related to CPR actions.Keywords: Pemberdayaan Masyarakat, Kegawatdaruratan, Sudden Cardiac Arrest.